An enhanced interface model for friction fatigue problems of axially loaded piles - Kullolli, Borana; Baeßler, Matthias; Cuéllar, Pablo; RICA, Shilton; Rackwitz, Frank (2019)
peer reviewed The shaft bearing capacity often plays a dominant role for the overall structural behaviour of axially loaded piles in offshore deep foundations. Under cyclic loading, a narrow zone of soil at the pile-soil interface is subject to cyclic shearing solicitations. Thereby, the soil may densify and lead to a decrease of confining stress around the pile due to micro-phenomena such as particle crushing, migration and rearrangement. This reduction of radial stress has a direct impact on the shaft capacity, potentially leading in extreme cases to pile failure. An adequate interface model is needed in order to model this behaviour numerically. Different authors have proposed models that take typical interface phenomena in account such as densification, grain breakage, normal pressure effect and roughness. However, as the models become more complex, a great number of material parameters need to be defined and calibrated. This paper proposes the adoption and transformation of an existing soil bulk model (Pastor- Zienkiewicz) into an interface model. To calibrate the new interface model, the results of an experimental campaign with the ring shear device under cyclic loading conditions are here presented. The constitutive model shows a good capability to reproduce typical features of sand behaviour such as cyclic compaction and dilatancy, which in saturated partially-drained conditions may lead to liquefaction and cyclic mobility phenomena.